ҚАЗАҚСТАН ХАЛҚЫНЫҢ СЕМІЗДІККЕ ШАЛДЫҒУЫНА ƏСЕР ЕТЕТІН ФАКТОРЛАРҒА АНАЛИЗ (Experimental biology, 2009)
Recently, in our republic there is an increase in the number of people with overweight, especially among the working population and children, so the problem of obesity is one of the important problems of medicine. The Program for Research on «Evaluation nutritional status and health of the population of Kazakhstan» - examined the role of inadequate nutrition and income levels as risk factors of obesity. The results show the influence of income as the value of BMI and the frequency of prevalence of overweight and obesity, which turned out to be higher among respondentswith high-income.
Keywords: BMI